Decreased of Family Negative Attitudes in Family Members of Schizophrenic Sickness disorder with Supportive Therapy - Kellyana Irawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Family negative attitudes and family rejection against family members with mental illness increased the incidence of recurrence in patients with mental disorder. The study aimed to determine the effect of supportive therapy on family attitudes and family rejection of family members with mental disorder schizophrenia. This study used a pre-post design quasi-experiment with control group with sampling using cluster sampling The numbers of sample in this study were 51 families with mental illness family member for the intervention group and 45 families with mental illness family member to the control group. This research used the instrument family attitude scale and acceptance and rejection scale. The results showed there were significant changes in attitudes after being given supportive therapy group (p-value<a=0.05). There is a significant difference in the change in the intervention group and the control (p-value<a=0.05). The suggestion of this research is to apply supportive group therapy and family communities.